Cardiovascular regeneration in non-mammalian model systems: What are the differences between newts and man? - Borchardt, Thilo; Braun, Thomas (Thrombosis and Haemostasis, 2007)
The mammalian heart cannot regenerate substantial cardiac injuries, while certain non-mammalian vertebrates such as certain fish (Danio rerio) and amphibiae (Notophthalmus viridescens) are able to repair the heart without functional impairment. In mammalians, the prevailing repair process is accompanied by fibrosis and scarring, while zebrafish and newts can replace lost contractile tissue by newly formed cardiac muscle with only little or no scar formation.A better understanding of cardiac regeneration in non-mammalian vertebrates might provide new insights for the manipulation of regenerative pathways in the human heart. Here, we summarize the current knowledge in cardiac regeneration of newts and the principal differences to repair processes in mammalian hearts.
Keywords: Newt; cardiac muscle; regeneration; dedifferentiation; proliferation